2015
DOI: 10.1210/jc.2015-1794
|View full text |Cite
|
Sign up to set email alerts
|

Declining Incidence of Medication-Related Osteonecrosis of the Jaw in Patients With Cancer

Abstract: The likelihood of developing MRONJ can be minimized through the implementation of prophylactic dental assessment and active dental intervention. This reinforces the importance of increased dental awareness and enhanced dental intervention in the prevention of MRONJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 29 publications
5
21
0
Order By: Relevance
“…The overall IP of BRONJ in the present study was 14.5%, agreeing the wide range of incidence previously reported in the literature (Fung et al, 2017;Khan et al, 2015;Ruggiero et al, 2009;Vidal-Real et al, 2015). The IP reduction of BRONJ was similar to that of other studies reporting reductions with preventive treatments from 26.3% to 6.7% (Dimopoulos et al, 2009), from 15.5% to 0% (Bonacina et al, 2011), and from 4.6% to 0.8% (Sim et al, 2015). Although these results are difficult to compare due to differences in study design including ambispective and retrospective studies, patient characteristics with different oncological diseases, different types of BP and other drugs, preventive dental treatment performed, follow-up time, sample size, and statistical analysis.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The overall IP of BRONJ in the present study was 14.5%, agreeing the wide range of incidence previously reported in the literature (Fung et al, 2017;Khan et al, 2015;Ruggiero et al, 2009;Vidal-Real et al, 2015). The IP reduction of BRONJ was similar to that of other studies reporting reductions with preventive treatments from 26.3% to 6.7% (Dimopoulos et al, 2009), from 15.5% to 0% (Bonacina et al, 2011), and from 4.6% to 0.8% (Sim et al, 2015). Although these results are difficult to compare due to differences in study design including ambispective and retrospective studies, patient characteristics with different oncological diseases, different types of BP and other drugs, preventive dental treatment performed, follow-up time, sample size, and statistical analysis.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis of BRONJ‐free survival showed that BRONJ developed within the first three years in 97% of patients in group A compared with 66% in group B ( p = .056), which can be considered clinically significant in accordance with the significant differences in actuarial incidence reported by Sim et al. (). The 3‐year HR of 36% was similar to that obtained by Boonyapakorn, Schirmer, Reichart, Sturm, and Massenkeil ().…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations